PERANCANGAN KURSI SET TERASDENGAN IDE DASAR BIJI KOPI - Achmad Zainudin; Ariyanto Ariyanto; Hamdan Muftian (SULUH: Jurnal Seni Desain Budaya, 2021)
The terrace is one part of the house that serves to connect the living room and the yard. Designing unique and different patio furniture is a good solution. This final project aims to design creative and innovative, unique, and suitable furniture designs in accordance with today's millennial needs.The design study begins with a qualitative research method with data collection techniques using literature study, observation and interviews. The next process is the design stage of analyzing data, conceptualizing, design sketches, work drawings, product processing and finishing processes.The design results of the patio chairs are the uniqueness of the shape of the chairs and tables with the coffee bean shape transformation technique, namely by changing the style, position, volume and dimensions of the shape elements but without leaving the original elements of the shape of the arabica coffee beans. In addition, the chairs and patio tables are designed using modern-style furniture products.